Formability of friction stir processed low carbon steels used in shipbuilding - Sekban, D. M.; Akterer, S. M.; Saray, Onur; Ma, Z. Y.; Purcek, G. (Journal Mater Sci Technol, 2018)
The stretch formability of a low carbon steel processed by friction stir processing (FSP) was studied under biaxial loading condition applied by a miniaturized Erichsen test. One-pass FSP decreased the ferritic grain size in the processed zone from 25 mu m to about 3 mu m, which also caused a remarkable increase in strength values without considerable decrease in formability under uniaxial loading. A coarse-grained (CG) sample before FSP reflected a moderate formability with an Erichsen index (EI) of 2.73 mm. FSP slightly decreased the stretch formability of the sample to 2.66 mm. However, FSP increased the required punch load (F-EI) due to the increased strength by grain refinement. FSP reduced considerably the roughness of the free surface of the biaxial stretched samples with reduced orange peel effect. The average roughness value (Ra) decreased from 2.90 in the CG sample down to about 0.65 mu m in fine-grained (FG) sample after FSP. It can be concluded that the FG microstructure in low carbon steels sheets or plates used generally in shipbuilding provides a good balance between strength and formability. (C) 2017 Published by Elsevier Ltd on behalf of The editorial office of Journal of Materials Science & Technology.
Keywords: Friction stir processing; Low carbon shipbuilding steel; Formability; Microstructure; Mechanical properties